A Case Report: 52 Year Old Peruvian Patient with Cystic Fibrosis - Pecho-Silva, Samuel (2020)
The Cystic fibrosis (CF) is an autosomal and recessive genetic disease. It affects much more frequently the population of Caucasian origin, where their incidence ranges from 1 in 3,000 in Caucasians to 1 in 8,000 in newly Hispanic live births. By 2018, 30,775 patients with cystic fibrosis, of them less than 10% of patients worldwide had more 40 years and none had been diagnosed after 40 years of age. We present below the case of a 52-year-old Peruvian adult with CF. This would be one of the patients with the latest diagnosis worldwide and the longest patient in Peru and one of the longest in Latin America.